Abdominal Cocoon: An Unusual Cause of Intestinal Obstruction - Paul, Tapesh Kumar; Lodi, Russel Ahmed Khan; Ali, Shayda; Basunia, Mohammad Arman Zahed; Rouf, Hasan Md Abdur (Delta Medical College Journal, 2017)
Abdominal cocoon, the idiopathic form of sclerosing encapsulating peritonitis, is a rare condition of unknown etiology that results in an intestinal obstruction due to total or partial encapsulation of the small bowel by a fibrocollagenous membrane. The early clinical features are nonspecific, are often not recognized and it is difficult to make a definite pre-operative diagnosis. Clinical suspicion may be generated by the recurrent episodes of small intestinal obstruction combined with relevant imaging findings and lack of other plausible etiologies. Surgery is important in the management of this disease. Careful dissection and excision of the thick sac with the release of the small intestine leads to complete recovery in the vast majority of cases. Here a case of abdominal cocoon in a 45 years old male is presented due to its rarity and difficulty in preoperative diagnosis. Delta Med Col J. Jan 2017 5(1): 49-52